고성군 숨치 복합 해양치유 프로그램의 폐 건강 개선 효과 - 김현준; 김성열; 박장준; 이시우; 신재숙; Kim, Hyun-Jun; Kim, Seong-Yeol; Park, Jang-Jun; Lee, Si-Woo; Shin, Jae-Suk (Journal of the Korean Society of Integrative Medicine, 2022)
Purpose : The study to verify the effectiveness of the Soomchi combined marine healing program by analyzing the physical composition of the subjects, their blood lipids, and the effects of the program on their lung health-related variables, and heart rate variability variables. Methods : In the experiment, the Soomchi combined marine healing program was conducted for 5 hours a day, 5 days a week. on 15 participants. The results of their body composition, blood lipids, lactic acid, blood pressure, PEF, FEV1 and maximum oxygen intake were analyzed before and after the subjects completed the Soomchi program. For the statistical analysis, the mean and standard deviation (M±SD) of each variable were calculated using SPSS version 20 and an independent t-test was conducted to test for the amount of change in the participants before and after the Soomchi combined marine healing program. All significant levels were set to α=.05. As a result of the experiment Results : First, no statistically significant differences were found in the changes in body composition after the 5-day combined marine healing program was completed. Second, regarding the changes in blood component after the program was conducted, statistically significant differences were found in the lactic acid (p<.05). That is, the experimental group showed a significant decrease in lactic acid after the program whereas the control group showed a significant increase. Third, systolic blood pressure decreased significantly and while in PEF and FEV1 increased significantly in the experimental group after the program. Fourth, the LF of the control group significantly decreased after 5 days. Conclusion : After the Soomchi Lung Health Ocean Healing Program, positive physical changes were observed in the lung health variables and heart rate variability of the participants.